2022
DOI: 10.3390/ijerph19074195
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Application of Chicken Eggshell Calcium to Improve the Functional Value of Gingerbread

Abstract: Food waste, such as eggshell, can be an environmental problem if it is not properly managed. One of the ways to solve this is by using the eggshell as the cheap calcium source in food products. Polish gingerbread fortified with chicken eggshell powder (ESP) calcium was developed to solve the eggshell waste problem and to reduce the risk of osteoporosis. This study focused on the effect of ESP addition on basic composition, sensory evaluation, and antioxidative activity of gingerbread. Two samples of gingerbrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 80 publications
1
10
0
7
Order By: Relevance
“…Przybylski et al [ 22 ] also found a high content of total polyphenols in gingerbread cakes after supplementation with tomato, beetroot, and pumpkin purée (39.02, 33.88, and 29.85 mg GA/100 g, respectively). On the contrary, similar TPC results were observed in gingerbread without (215.59 mg GA/100 g) and fortified with 3% chicken eggshell powder (214.01 mg GA/100 g) [ 3 ].…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…Przybylski et al [ 22 ] also found a high content of total polyphenols in gingerbread cakes after supplementation with tomato, beetroot, and pumpkin purée (39.02, 33.88, and 29.85 mg GA/100 g, respectively). On the contrary, similar TPC results were observed in gingerbread without (215.59 mg GA/100 g) and fortified with 3% chicken eggshell powder (214.01 mg GA/100 g) [ 3 ].…”
Section: Resultssupporting
confidence: 58%
“…In addition, the DPPH (9.25 μM/g) and ABTS values (9.42 μM/g) of shortbread and wheat flour cookies fortified with elderberries were higher than scavenging activity of control samples (DPPH = 2.60 μM/g and ABTS = 1.11 μM/g) [ 51 , 53 ]. Unexpectedly, the addition of 3% eggshell powder to the gingerbread samples caused a decrease in their antioxidant properties (DPPH = 388.13 and 370.44 mg TE/100 g, and ABTS = 453.79 and 448.82 mg TE/100 g for control and enriched samples, respectively) [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second part explored the effect of CESP fortification on the physicochemical and sensory acceptance of madeleine cakes. Baked goods were considered an acceptable food vehicle to incorporate CESP as it would minimally modify the organoleptic properties of the resulting products (Arnold et al. , 2022).…”
Section: Methodsmentioning
confidence: 99%